SERIAL MONITORING OF BLOOD GLUCOSE USING THE AISYCARE_GULAMU APPLICATION FOR THE T2DM BACK-REFERRAL PROGRAM - Bagus Aulia Mahdi; Putri Purnamasari Husein; Andri Tirta; Natasya Bilqis Khayyil Rahmadinah (Biomedika, 2026)
T2DM is a major problem in health services in Indonesia through the NHI system. The determination of back-referrals frequently presents a contentious issue between BPJS-FKTP and FKTL. The AisyCare-GulaMU application is an Android-based tool designed for the IT-based monitoring of blood glucose levels in T2DM patients who are PRB. The research was performed on a retrospective cohort of NHI patients diagnosed with T2DM in an outpatient setting during the initial six months of 2025 with pre and post analysis glucose profile. There are significant reduction in blood glucose serial monitoring 1st to 2nd month (p=0.002), 2nd to 3rd month (p=0.027)  and hba1c after third month treatment (p=0.000). There also significant blood glucose(p=0.002) and hba1c (p=0.000) for group back referral and not to refer. The AisyCare-GulaMU application enables the assessment of patients' blood sugar levels on a monthly basis, facilitating the determination of subsequent service directions. The AisyCare-GulaMU application allows for effective monitoring of T2DM patients' treatment progress, enabling BRP to operate efficiently.